Transformasi Iman dari Personal ke Komunal dalam Kitab Ratapan: Studi Hermeneutik terhadap Ratapan 3 dan 5 - Joel Amadeus Brilian (Predica Verbum: Jurnal Teologi dan Misi, 2025)
This study aims to identify and analyze the process of faith transformation from the personal to the communal realm in the Book of Lamentations, particularly chapters 3 and 5. Using interpretive qualitative methods and a structural-literary hermeneutical approach, this study examines poetic patterns, rhetorical dynamics, and key verses that mark changes in expressions of faith. The results of the study show that Lamentations 3 displays a deep reflection of personal faith and becomes a turning point for the spiritual transformation of the people. Key verses such as Lamentations 3:21-22 and 3:40 show a shift from lamentation to a collective call for self-correction and hope in God. This process reaches its peak in Lamentations 5, which is a response and expression of faith and a collective plea for God's sovereignty amid destruction. The main conclusion of this study is that personal faith filled with reflective space can be a source of restoration and strength for the community as a whole. Of course, this study makes an important contribution in seeing suffering not as an ending but as a transformative space for the growth of faith, both personally and communally.